Fetal macrosomia at the University College Hospital, Ibadan: a 3-year review (2003)
The study aimed to determine the maternal characteristics and contribution to obstetric morbidity of infants presenting with fetal macrosomia at the University College Hospital, Ibadan. This was a retrospective study. Obstetric data of the mothers were extracted from the casenotes and analysed. Fetal characteristics such as sex and weight, and perinatal complication were also analysed. The maternal characteristics that were significantly different in the study and control groups were parity, term weight ≥90 kg, previous history of fetal macrosomia and mean duration of pregnancy. There was no significant difference in maternal age or height. The incidence of caesarean section was three times more common in the study group. There were three cases of shoulder dystocia in the study group but none in the control group. The mean birth weight of macrosomic babies delivered by section or macrosomic babies that died was higher than the mean birth weight of macrosomic babies delivered per vagina or that survived. Severe asphyxia at 1 minute was significantly higher in the study group. Perinatal mortality among macrosomic babies was 11.4/1000. There was no mortality in the control group. It is suggested that clinical suspicion of macrosomic based on risk factors such as those identified in this study may be found useful in antenatal prediction.